Toxicological studies on Acanthus montanus leaf extracts in male and female albino rats - Iwueke, V. Adaku.; Chukwu, C. Ezinne.; Onuoha, U. Obinna.; Osuocha, K.U. (African Science Publications, 2021)
Leaves of Acanthus montanus have been used traditionally in treatment of several diseases such as skin diseases. This work was designed to evaluate toxicological impact of A. montanus extracts in male and female albino rats. Ninety (90) albino rats of 45 male and 45 female rats were used for the study, divided into 18 groups of five rats. Alphabets and figures were used to identify the male and female rats. Groups A and 1 received normal rat chow, Groups B and 2, C and 3, D and 4, E and 5 received 200, 400, 600 and 800 mg/kg of aqueous extract of A. montanus leaves while groups F and 6, G and 7, H and 8, I and 9 received 200, 400, 600 and 800 mg/kg of methanol extract of A. montanus. Liver enzyme assays showed a dose dependent significant increase in the test groups while total protein and albumin showed significant decrease in the test groups. Total and direct bilirubin did not show significant difference in test groups compare to control. Creatinine level showed significant increase (p ≤ 0.05) in test groups while urea decreased in test groups. The histo architecture of liver and kidney, showed moderate to widespread impairments in the groups exposed to 800 mg/kg of aqueous extract, 400, 600 and 800 mg/kg of methanol extract. A. montanus leaves may exhibit renal and hepatic impairment with increased dosage; hence should be detoxified before usage.
Keywords: Acanthus, Montanus, Toxicological, Albino rats